The Effect of Imagery Training on The Results of Male Volleyball Athletes’ Jump Service - Tegar Pramudia Laksana; Ira Purnamasari M. Noors; Yopi Kusdinar; Mulyana (Universitas Negeri Semarang, 2025)
Volleyball is a team game that is already popular among the public, which emphasizes good physical, technical, and psychological skills . Research This aiming For examine the effect of imagery training on the results of male volleyball athletes’ jump service . Research methods This use method experiment with design study One Group Pretest Posttest Design involving 12 volleyball athletes son of Tectona Bandung club. Election sample use technique purposive sampling , with treatment as many as 8 meetings in a way intensive . Instrument study use service accuracy test (AAHPER) Service Accuracy is an instrument used to collect athlete data. before and after given treatment . After the data is obtained , it is analyzed use SPSS version 21 uses the paired sample T-test. Based on results data processing shows that Sig.(2tailed) value of 0.000 < 0.05. The results of the pretest-posttest and the overall difference in athletes obtained a pretest score of 98 %, then there was an increase in the posttest of 102 % with an average difference of 4%. Imagery Training has beeb proven to have significant effect on improving jump service skills in male volleyball athletes, through strengthening technical, biomechanical, psychological, and motot aspect.